Research and Application of the Key Part Design Method of Minor Double Input Planetary Gear Reducer - Xu Ke; Zhang Qing (Jixie chuandong)
The theoretical analysis and calculation of gear tooth of two- input planetary reducer used in aerospace craft steering engine are carried out by using the general mechanical design method and by disposable mechanical design method separately. Through analysis of the result,when the condition cannot meet the strength requirement by using general mechanical design method,the theoretical security coefficient calculated by using the disposable mechanical design method is 3. 96 under the same conditions. The performance test of the prototype reducer shows that the double planetary gear reducer meets the design requirements. It turns out that the disposable mechanical elements design theory is fairly effective and practical.